BMS545: Immunology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2022)
This course provides the basic concepts on how the body’s immune system functions. The principles of innate and adaptive immune response including the various components involved and the cellular and molecular mechanisms of antigen recognition and host response to antigens in both innate and adaptive immunity. are discussed at length. The principle and importance of immunization are also included in this course. Emphasis is also given to the principles and application of immunological techniques in disease diagnosis and quantification of antigens and antibodies.